Geomorphological characteristics and the kinematic process of the Ganheba rock–ice avalanche in Yulong Mountain, China - Chen, Ruichen; Chen, Jian; Shi, Lulu; Cui, Zhijiu; Chen, Song (Frontiers in Earth Science, 2023)
Rock–ice avalanches have increased in recent years due to global warming. On 12 March 2004, a massive failure of rock mass (9.1×106 m3) originated on the south slope of Yulong Mountain in Yunnan Province and eventually formed the Ganheba rock–ice avalanche, with an H/L ratio of 0.4. In this study, the geomorphological characteristics, sedimentary characteristics, and emplacement process of the Ganheba rock–ice avalanche were analyzed based on remote sensing interpretation, field investigation, and 2D discrete element modeling. This study suggests that long-term effects, including historical seismic effects and freeze–thaw action, were the key factors in the occurrence of this landslide. Interesting landforms and sedimentary structures found in this case, such as lateral ridges, superelevation, and boat rocks, were used to explain the characteristics of the velocity and the thinning spreading process of the avalanche mass. The numerical simulation further revealed that the entire movement of this rock–ice avalanche lasted about 105 s, with a maximum front velocity of 82 m/s. The underlying substrate rather than the ice is considered to have contributed to the hypermobility of the Ganheba rock–ice avalanche. The developed fissures, complex topography, and basal friction were determined to control the progressive fragmentation in this case. Meanwhile, the kinematic process of the Ganheba rock–ice avalanche was divided into four stages: failure and acceleration, collision deceleration, deceleration spreading, and deformation. The findings of this study contribute to an understanding of the evolution of glacier-related hazards in the high-mountain region.